Islam dan Kearifan lokal (Perspektif Teologis Hubungan antara Agama dan Budaya di Kampung Naga) - Nurrohman -; Abd Hannan EF (Al-Tsaqafa : Jurnal Ilmiah Peradaban Islam, 2017)
Since its birth, Islam can not be separated from traditions and cultures. Not all local traditions and cultures are rejected or destroyed by Islam, as long as it does not deviate from the basic principles of Islam. This is what is called the uruf in the Qur'an. However, since the emergence of puritanic Salafi Wahabism, the tradition which still associated with the previous religion, such as Hindu and Buddha, often stigmatizwed as syncretic, heretic and not properly and completely practiced sharia. The focus of the study is to describe the relationship between religion and culture in Muslim community living in Kampong Pulo and Kampung Naga. The type of research is decricptive explanatory. Data was collected from documents or library, observation and interview with several figures which were purposively chosen. The type of data consisted: 1) a brief history of this community, 2) the religious system of this community 3) the forms of local wisdom practiced by this community. These data will be analized to explain how religion and culture build harmonious relationship, and then it also be analized further to determine the kind of theology and the model of sharia that was practiced.